Aminophylline exhibits convulsant action in rats during ontogenesis - Mares, P; Kubová, H; Czuczwar, S J (Brain & development, 1994)
Aminophylline-induced seizures were studied in 166 male albino rats in five age groups--7, 12, 18, 25 and 90 days old. Aminophylline injected in doses from 150-350 mg/kg i.p. elicited both minimal, clonic and major, i.e. generalized tonic-clonic seizures during the 60-min observation period. The pattern of minimal seizures did not change during development; major seizures exhibited changes in proportion to their three phases--running, tonic and clonic phases. Dependence on the dose of aminophylline was observed in the incidence of major seizures as well as in shortening of latencies of both types of seizures. More marked convulsant effects of aminophylline in 7-, 12- and 18-day-old rat pups than in older animals might be due to pharmacokinetic as well as pharmacodynamic factors.
Keywords: konvulziva; chování zvířat; aminofylin; epilepsie tonicko-klonická; LD50; Dose-Response Relationship, Drug; Epilepsy, Tonic-Clonic; Convulsants; stárnutí; krysa rodu Rattus; zvířata; Aging; potkani Wistar; Aminophylline; Rats, Wistar; Male; Lethal Dose 50; Rats; vztah mezi dávkou a účinkem léčiva; Animals; mužské pohlaví; Behavior, Animal